Pituitary disease and anaesthesia. Issue 6 (June 2020) - Appleby, Ian; John, Robert; Hirsch, Nicholas
Abstract: Patients with pituitary gland tumours comprise a significant proportion of the neurosurgical population, making transphenoidal pituitary surgery a relatively common procedure. These patients present unique anaesthetic challenges resulting from hormone hypersecretion, pituitary hypofunction or tumour mass effect. To understand this pathophysiology requires knowledge of normal pituitary anatomy and physiology. Respiratory and cardiovascular sequelae of pituitary tumours also pose anaesthetic challenges. We aim to review the key principles involved in the preoperative assessment, intraoperative management and postoperative care of these patients.